2001
DOI: 10.1002/1521-3951(200102)223:3<635::aid-pssb635>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Determination of Shallow Electronic States Bound by Dislocations in Semiconductors

Abstract: Using a plane wave basis, we have solved numerically the Schrö dinger equation of the envelope function in the case of dislocation strain field binding potentials (deformation and piezoelectric coupling). Shallow one-dimensional bands are found for both electrons and holes, characterised by larger binding energies than those previously found by approximated analytical methods, 1D dislocation bands have also been computed and show a splitting of light and heavy hole bands resulting into four distinct bands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…According to theoretical work based on effective mass theory and deformation potentials, the shear stresses will not affect the s-type conduction band minimum but only the p-type valence band maximum. Thus, such screw dislocations would bind exclusively holes [6,9]. Excitons then are formed by binding electrons to these bound holes by Coulomb interaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to theoretical work based on effective mass theory and deformation potentials, the shear stresses will not affect the s-type conduction band minimum but only the p-type valence band maximum. Thus, such screw dislocations would bind exclusively holes [6,9]. Excitons then are formed by binding electrons to these bound holes by Coulomb interaction.…”
mentioning
confidence: 99%
“…However, they may, due to the limited size of presently computable supercells, fail in correctly describing bound states due to the long-range strain field appropriately. Continuum approaches based on the effective mass approximation and deformation potentials (e.g., k · p calculations, or numerical solutions of the Schrödinger equation [6,9]) are appropriate to provide a reliable and accurate description of the bound states due to the long-range strain field. A major drawback of treating shallow states due to the long-range strain field by a continuum approach is the treatment of the high strain close to the dislocation core.…”
mentioning
confidence: 99%
“…Therefore, the lattice distortion, introduced by the dislocation strain field and self-consistently taken into account in the ab initio calculations, may be supposed to be at the origin of the shallow states in the gap. This hypothesis was proposed and confirmed in the works presented in [29,30], that solved both numerically and analytically the Schrödinger equation of the envelope function in the presence of the dislocation strain field binding potential and found that these circumstances lead to the formation of shallow one-dimensional bands for both electrons and holes in the energy gap. According to [29,30], in GaN, the electronic bound states due to the dislocation deformation potential should lie at ∼100 meV below the conduction band.…”
Section: Introductionmentioning
confidence: 58%
“…This hypothesis was proposed and confirmed in the works presented in [29,30], that solved both numerically and analytically the Schrödinger equation of the envelope function in the presence of the dislocation strain field binding potential and found that these circumstances lead to the formation of shallow one-dimensional bands for both electrons and holes in the energy gap. According to [29,30], in GaN, the electronic bound states due to the dislocation deformation potential should lie at ∼100 meV below the conduction band. Also, this last result was confirmed through ab initio calculations performed on big clusters (∼60 000 atoms) [31], which showed that the core orbitals are fully reconstructed leading to core structures in agreement with HR-TEM pictures and eliminating the possible existence of any deep states.…”
Section: Introductionmentioning
confidence: 58%
“…The Kohn-Sham matrix eigenelements are then numerically solved using an iterative procedure and their eigenvalues allow us, finally, to calculate the full quantum well energy E T (L) which turns out to be a function of the parameter L. This last value L is chosen so as to minimize E T . This variational procedure, already used in [14,15], allows one to get precise numerical results with a relatively low number of plane waves (∼50 in the present 1D localized case). Figure 3 illustrates the first two wavefunctions found in the case of the triangular potential shown in figure 1.…”
Section: Numerical Determination Of the Quantum Well Energy Statesmentioning
confidence: 99%